Impact of Sensory Perceptions on the Urge to Buy Impulsively - Pooja Goel (2360743) (2023)
E-commerce retailers use augmented reality (AR) based apps for product presentations. This study investigates the influence of sensory perceptions in an urge to buy impulsively (UBI). This study further examines the mediating role of emotional states in the relationship between sensory perceptions and UBI. It also examines whether involvement moderates the impact of emotional states on the UBI. Data were collected from users who have used augmented reality (AR) features in Lenskart App and purchased products at least once during the last two months. Overall, the sensory perceptions elicited by AR apps significantly influence customers’ emotional states, driving the UBI. The influence of emotional states on the UBI was also considerably moderated by product involvement. Several practical and theoretical implications for e-commerce retailers are also discussed. Other Information Published in: Journal of Computer Information Systems License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/08874417.2023.2224748